Flow cytometric basophil activation tests: Staining of exteriorized basophil granule matrix by fluorescent avidin versus appearance of CD63. Issue 6 (3rd February 2020) - Ebo, Didier G.; Elst, Jessy; van Houdt, Michel; Pintelon, Isabel; Timmermans, Jean‐Pierre; Horiuchi, Tatsuo; Faber, Margaretha A.; Hagendorens, Margo M.; Mertens, Christel M.; Sabato, Vito
Abstract: Background: Staining of exteriorized basophil granule matrix by fluorescent avidin might be a reliable technique to monitor basophil degranulation. This study compares the avidin‐based technique with the upregulation of CD203c and appearance of CD63 in response to various stimuli. Methods: Fourteen individuals responsive to anti‐IgE, nine healthy controls, and five birch pollen‐allergic patients, and five nonresponders were studied. Activation experiments included anti‐IgE, fMLP, interleukin‐(IL)‐3, and birch pollen allergen. Basophil activation/degranulation was analyzed by flow cytometry and microscopy using anti‐CD63, anti‐CD203c, and avidin. Results: Stimulation with anti‐IgE, fMLP, and relevant allergen results in upregulation of CD203c, CD63 appearance, and an increase in avidin binding. In response to anti‐IgE and allergen, upregulation of CD203c peaks within 10 min, CD63 and avidin binding reach a plateau after 10–20 min. CD63 staining leads to a bimodal distribution, avidin staining causes a unimodal shift with a less clear discrimination between degranulating and nondegranulating cells. In response to fMLP, upregulation of CD203c and CD63 and avidin binding are maximal after 2.5 min. Following incubation with anti‐IgE and fMLP, percentages of CD203c+ cells are higher than those of CD63+ and avidin+ cells, pointing to a dissociation between activation and degranulation. Percentages of CD63+ cells are systemically higher than those of avidin+ cells. Incubated with IL‐3 only upregulates CD203c, while no CD63 or avidin binding is observed. Conclusions: Staining of exteriorized proteoglycans by avidin is a reliable technique to quantify basophil degranulation but offers no added value when compared to traditional assays that use CD63 as a readout.